Providing educational videos and posters for COVID-19 self-isolating patients at home in the telemedicine program of the National Agency for Disaster Countermeasure (BNPB) Special Region of Yogyakarta (DIY) - Ananda, Vidya; Muchti, Firmansyah Aditya; Widyatama, Rendra (BKM Public Health and Community Medicine, 2021)
Objective: COVID-19 in Indonesia spawned a second wave in June-August 2021 and packed the hospitals, making the COVID-19 patients with mild or no symptoms have to self-isolate at home. However, the patient's condition often changed rapidly and worsened, so regular monitoring was needed to prevent death during self-isolating. The BNPB DIY Health Care Task Force formed a Telemedicine Team to monitor patients online with detailed information on doing self-isolation safely at home. Its Media Team created educational videos and posters as effective educational media. Contents: The Media Team consisted of presenters, scriptwriters, videographers, and graphic designers. It determined the topic of the content of the video messages and posters based on what information is needed and must-known by the patient during self-isolation. After that, the coordinator and manuscript writer collected evidence-based data and relevant regulations. The information included the emergency signs during self-isolating and medicines needed to prepare. It also had information on how to measure body temperature and oxygen levels using an oximeter, use a blood pressure meter, do prone position if short of breath, sunbathe, and tips on training the sense of smell in patients with anosmia. As a volunteer for the BNPB DIY Health Care Task Force Thickening to patients who were self-isolating at home, the doctor conveyed all the information compiled. The duration of the video was 1-5 minutes, equipped with supporting footage. The video results were uploaded through the BNPB DIY Task Force's Instagram and Youtube accounts and also shared through Whatsapp so that self-isolating patients could easily access and download them. Information also visualized the material in the form of posters. From the evaluation, the patient felt helped and understood all the information in the message and could practice it easily. Tujuan: Covid-19 di Indonesia telah memunculkan gelombang kedua pada Juni-Agustus 2021 dan menyebabkan rumah sakit penuh. Keadaan tersebut membuat pasien Covid-19 bergejala ringan atau tanpa gejala harus melakukan isolasi mandiri (isoman) di rumah. Namun, kondisi pasien kerap berubah cepat mengalami perburukan, sehingga perlu dipantau secara berkala guna mencegah kematian saat isoman. Situasi tersebut mendorong Satgas Penebalan Nakes PNPB DIY membentuk Tim Telemedicine untuk memantau pasien secara daring berupa informasi detail bagaimana melakukan sioman dengan aman di rumah, serta membuat media edukasi terkait Covid-19. Untuk keperluan tersebut, Tim Media membuat video edukasi dan poster sebagai media edukasi yang efektif. Isi: Tim Media terdiri dari pemateri, penulis naskah, videographer dan desain grafis. Tim Media menentukan topik isi pesan video dan poster berdasarkan informasi apa saja yang diperlukan dan wajib diketahui pasien selama isoman. Setelah pemilihan topik, kordinator dan penulis naskah mengumpulkan informasi berdasarkan bukti ilmiah (evidence based) dan dengan mendasarkan diri pada berbagai peraturan yang relevan. Informasi yang dikumpulkan meliputi apa saja tanda kegawatan saat isoman, obat-obat apa yang harus disiapkan, bagaimana cara mengukur kadar oksigen menggunakan oksimeter dengan benar, bagaimana menggunakan tensi meter, bagaimana mengukur suhu tubuh dengan baik, cara melakukan prone position jika sesak napas, bagaimana cara berjemur, sampai tips melatih indera penciuman pada pasien yang mengalami anosmia. Semua informasi yang disusun disampaikan dokter sebagai relawan Satgas Penebalan Nakes BNPB DIY kepada pasien yang melakukan isoman di rumah. Durasi video relatif singkat yaitu 1-5 menit, dilengkapi footage yang mendukung. Hasil video diunggah melalui akun Instagram dan Youtube Satgas BNPB DIY agar dapat diakses pasien isoman dengan mudah, termasuk didownload oleh pemantau guna dikirimkan untuk pasien isoman melalui aplikasi Whatsapp. Materi video juga divisulisasikan dalam bentuk poster. Dari evaluasi yang dilakukan, pasien merasa terbantu dan mengerti informasi semua isi pesan serta dapat mempraktekkannya dengan mudah.